STABILITY INDICATING METHOD DEVELOPMENT AND VALIDATION OF FIMASARTAN BY REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY IN BULK AND PHARMACEUTICAL DOSAGE FORM - A, SRUTHI; PRASAD PANIGRAHY, UTTAM (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: A rapid, sensitive and specific reverse phase High performance liquid Chromatography (RP-HPLC) method was developed for the estimation of Fimasartan in bulk and pharmaceutical dosage form. Method: The RP-HPLC analysis was performed isocratically on a Primacel C18 column (150 mm × 4.6 mm internal diameter, 5 μm particle size) using mobile phase of composition Acetonitrile and 0.1% orthophosphoric Acid in 80:20, v/v proportions with a flow rate of 0.8 ml/min. Results: The analyte was monitered with UV-detector at 265 nm. In the developed method Fimasartan elutes at a typical retention time of 2.4 min. The proposed method is having linearity in the concentration ranging from 5-30 μg/ml of Fimasartan. Conclusion: : The method was statistically validated and had been applied to analysis of the drug in bulk and pharmaceutical dosage form.